Artificial Ice Hockey, Culture, and Commerce - Gruneau, Richard; Whitson, David (University of Toronto Press, 2019)
Artificial Ice explores how hockey has moved from popular pastime to commercial entertainment product, and one struggling to maintain its stature in the North American entertainment market. Contributors to Artificial Ice discuss the changing character of "major league" sports in North America, the strategic mistakes of the NHL in trying to enlarge its US presence, the importance of television to the economics of sports today, and the role of luxury sports facilities in the new "downtown" economy. The book highlights profound social and cultural changes within hockey, as well as in the global market for sporting spectacles